Analisis Strategi Pembelajaran Sejarah Kebudayaan Islam dalam Mengembangkan Berpikir Kritis Siswa Jenjang Tsanawiyah - Erwin Sugianto; Eva Siti Faridah (STAI Al-Hamidiyah Jakarta, 2026)
Along with the development of the times and demands of the 21st century, students are required to not only master high-level thinking skills (soft skills), namely critical thinking skills. Islamic Cultural History Education (SKI) often faces challenges in teaching methods that tend to be conventional and centered on memorization, which hinders the development of students' critical thinking skills, so it is important to apply strategies in learning Islamic cultural history. Learning strategies implemented by SKI teachers at MTs Al-Wutsqo Depok to develop students' critical thinking skills with interactive methods, discussions, debates, questions and answers, watching. argumentation approach. This study uses a qualitative method with a case study approach with data collection through observation, interviews and documentation. The results of data collection show that the critical thinking skills of grade VII students at MTs Al-Wutsqo Depok based on test results are 40% in the very good category with a value range of 80-100, while 60% are in the good category with a value range of 70-80. The ability of seventh grade students at MTs Al-Wutsqo Depok as observed during the teaching and learning process is 27% in the very good category, 20% in the good category, 20% in the sufficient category and 33% in the less category. With indicators of students' ability to draw conclusions in observations is 93%, the ability to identify assumptions is 80%, the ability to think deductively is 53%, the ability to make logical interpretations is 60%, the ability to evaluate which arguments are weak is 60%. Students' critical thinking abilities based on the results of the religious knowledge scores of seventh grade students at MTs Al-Wutsqo Depok, show that the implementation of learning strategies so far has been able to improve students' critical thinking abilities, although there are still differences in achievement in each critical thinking indicator.